Strategies for Teaching Reading Comprehension - Martina Napratilora (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2024)
Reading comprehension refers to getting meaning from what we have read from written information. Teaching reading comprehension is different from teaching reading. In reading comprehension, the readers do not read the text but also have to comprehend the reading passage. The educators use teaching and learning strategies but in teaching activities, they are confused about choosing an appropriate strategy for their students. Consequently, the students still feel bored, inactive, uninterested, and difficult to read passages. Therefore, the teachers have to create a better learning environment and be more creative and effective by using various strategies in teaching and learning activities because using appropriate strategies in the teaching and learning process will help the students reach better comprehension and also easier to reach learning purposes.